If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(y + -1) + -1(3 + y) = 5 + -6y + 8y Reorder the terms: 10(-1 + y) + -1(3 + y) = 5 + -6y + 8y (-1 * 10 + y * 10) + -1(3 + y) = 5 + -6y + 8y (-10 + 10y) + -1(3 + y) = 5 + -6y + 8y -10 + 10y + (3 * -1 + y * -1) = 5 + -6y + 8y -10 + 10y + (-3 + -1y) = 5 + -6y + 8y Reorder the terms: -10 + -3 + 10y + -1y = 5 + -6y + 8y Combine like terms: -10 + -3 = -13 -13 + 10y + -1y = 5 + -6y + 8y Combine like terms: 10y + -1y = 9y -13 + 9y = 5 + -6y + 8y Combine like terms: -6y + 8y = 2y -13 + 9y = 5 + 2y Solving -13 + 9y = 5 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -13 + 9y + -2y = 5 + 2y + -2y Combine like terms: 9y + -2y = 7y -13 + 7y = 5 + 2y + -2y Combine like terms: 2y + -2y = 0 -13 + 7y = 5 + 0 -13 + 7y = 5 Add '13' to each side of the equation. -13 + 13 + 7y = 5 + 13 Combine like terms: -13 + 13 = 0 0 + 7y = 5 + 13 7y = 5 + 13 Combine like terms: 5 + 13 = 18 7y = 18 Divide each side by '7'. y = 2.571428571 Simplifying y = 2.571428571
| -15+-30=-12-6 | | y+7=15/-8x-3 | | 7x^6+x^2-7x=0 | | 3/1-x/7=-2 | | x+x(.50-.60)=450 | | 6y+y^2=4 | | 5n=21+4b | | 6y+y^2=6 | | 9-3/8 | | 6(2x-8)+3=14 | | 9^3x*8^2x=1/36 | | 2/3=x/2+1/4 | | (q+4)(q-6)= | | 8x+5x=52 | | x-(2-x)=-2(2x-4) | | 9z^2-9z-9=0 | | y^2=y+12 | | n/6+48=62 | | 20+8x-5=8x+21 | | 8000+8000(.20-x)=7200 | | 59=7+4m | | 10x-5=25whatx | | -5x^2+450x-10000=0 | | -5x-3y=12 | | -10y+18=-15y-2+5y | | 5x+10-10=30 | | x^2-5xy+y^2=4 | | 3x-6=6x-36 | | 11x+16=6x+81 | | (2y+1)/4=(y-3)/3 | | (2y+1)/4=(y-3)/3 | | 4x/2x^2 |